Orthogonal space-time block code with pulse shaped offset QAM for multiple transmit antennas - Zhong, Kun. (2010)
In this thesis, a novel multiple-antenna scheme of combining real orthogonal spacetime block codes (O-STBC) with offset QAM is proposed. For any number of transmit antennas, this scheme is able to achieve full diversity with a code rate of unity and allows separate symbol-by-symbol PAM decoding on the in-phase (I) and quadrature (Q) channels. The pulse shape of the offset QAM signal and the I/Q-channel O-STBCs are shown to play an important role in the error performance of the scheme. In order to ensure that the bandwidth efficiency of this new scheme is comparable to that of systems employing conventional space-time block codes with non-offset modulation, the pulse shape of the offset QAM signal has to introduce controlled interferences between the I/Q channels. The amplitude of the interferences has an upperbound that is jointly determined by the pulse shape amplitude at half a symbol time, the sizes of the I/Q-channel PAM modulations and the I/Q-channel real O-STBCs. An analysis of the bit error rate of the system, subject to the constraint that the I/Q-channel PAM symbols be detected separately and individually, reveals the criteria under which the joint design of the pulse shape, the I/Q-channel PAM signal constellations and the I/Q-channel O-STBCs is able to achieve both full diversity and large coding gain.